The Hindu way: an introduction to Hinduism - Tharoor, Shashi (Aleph Book Company, 2019)
Starting with an examination of his own belief in Hinduism. Tharoor ranges far and wide in his study of the faith. He talks about the great souls of Hinduism, Adi Shankara, Patanjali, Ramanuja, Swami Vivekananda, Ramakrishna Paramahamsa and many others who made major contributions to the essence of Hinduism.